2012
DOI: 10.1037/a0027225
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity overrides complexity in rhythm perception: A cross-cultural comparison of American and Turkish listeners.

Abstract: Despite the ubiquity of dancing and synchronized movement to music, relatively few studies have examined cognitive representations of musical rhythm and meter among listeners from contrasting cultures. We aimed to disentangle the contributions of culture-general and culture-specific influences by examining American and Turkish listeners' detection of temporal disruptions (varying in size from 50-250 ms in duration) to three types of stimuli: simple rhythms found in both American and Turkish music, complex rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 45 publications
6
80
1
Order By: Relevance
“…Several studies have shown cultural differences in rhythmic perception tasks, indicating cultural influences on music cognition that are developed through listening and perceptual musical experiences which vary in different cultures (Hannon, Soley, & Ullal, 2012;Hannon & Trehub, 2005). For example, the study by Hannon et al (2012) showed that Turkish listeners performed comparably when detecting disruptions on a simple and complex rhythm task whereas American listeners performed less accurate on the complex compared to the simple rhythm task. The results are explained by the fact that Turkish music makes use of complex rhythmical patterns whereas American music mostly relies on simple rhythms.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown cultural differences in rhythmic perception tasks, indicating cultural influences on music cognition that are developed through listening and perceptual musical experiences which vary in different cultures (Hannon, Soley, & Ullal, 2012;Hannon & Trehub, 2005). For example, the study by Hannon et al (2012) showed that Turkish listeners performed comparably when detecting disruptions on a simple and complex rhythm task whereas American listeners performed less accurate on the complex compared to the simple rhythm task. The results are explained by the fact that Turkish music makes use of complex rhythmical patterns whereas American music mostly relies on simple rhythms.…”
Section: Discussionmentioning
confidence: 96%
“…This indicates that Western listeners have difficulty perceiving rhythmic patterns with complex-integer ratios primarily because they are inconsistent with familiar, simple meters. On the other hand, even listeners who are familiar with complex meters have difficulty processing sequences composed of highly complex integer ratios such as 7∶4 [25]. Interestingly, even infant listeners, who tend to exhibit less cultural bias, have difficulty with highly complex rhythms [26], as do trained musicians [14], suggesting that non-isochronous meters and complex-ratio rhythms might be categorically different from other meters [27] and intrinsically challenging to the human perceptual system.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research has shown that rhythms that are more familiar to some listeners will appear less complex to these listeners than rhythms with which they are unfamiliar (Snyder, Hannon et al, 2006). For example, metrical structures that involve nonisochronous beats (e.g., Balkan music) are not necessarily detrimental to task performance for enculturated listeners, as attested by recent developmental and cross-cultural studies on meter perception (Hannon, Soley, & Ullal, 2012;Hannon & Trehub, 2005a;Hannon & Trehub, 2005b;Hannon, Vanden Bosch der Nederlanden, & Tichko, 2012). Based on these findings, we may speculate on the influence of culture-specific expertise on the cognitive processing of temporal structures (Iversen, Patel, & Ohgushi, 2008).…”
Section: Mensural Determinacymentioning
confidence: 83%